Pengaturan Perang dan Konflik Bersenjata dalam Hukum Humaniter Internasional - Sulistia, Teguh (UI Scholars Hub, 2021)
War and armed conflicts have been the major problems in international law especially for their dejected impacts such as physical, psychological, and material loss for the victims. Wars and armed conflicts are subject to international humanitarian law so that people are protected from the soldiers’ violence where they kill each other in defending their national interests. Humanitarian law also has a purpose to protect wounded soldiers and prisoners of war from inhuman treatments. However, these wars and armed conflicts shoul be prevented because they have more disadvantages than advantages to human beings.